Characteristics and Outcome of Cancer Patients Admitted to the ICU in England, Wales, and Northern Ireland and National Trends Between 1997 and 2013*. Issue 10 (October 2017) - Ostermann, Marlies; Ferrando-Vivas, Paloma; Gore, Carmen; Power, Sarah; Harrison, David
Abstract : Objective: To describe trends in outcomes of cancer patients with an unplanned admission to the ICU between 1997 and 2013 and to identify risk factors for mortality of those admitted between 2009 and 2013. Design: Retrospective analysis. Setting: Intensive Care National Audit & Research Centre Case Mix Programme Database including data of ICUs in England, Wales, and Northern Ireland. Patients: Patients (99, 590) with a solid tumor and 13, 538 patients with a hematological malignancy with an unplanned ICU admission between 1997 and 2013; 39, 734 solid tumor patients and 6, 652 patients with a hematological malignancy who were admitted between 2009 and 2013 were analyzed in depth. Interventions: None. Measurements and Main Results: In solid tumor patients admitted between 2009 and 2013, hospital mortality was 26.4%. Independent risk factors for hospital mortality were metastatic disease (odds ratio, 1.99), cardiopulmonary resuscitation before ICU admission (odds ratio, 1.63), Intensive Care National Audit & Research Centre Physiology score (odds ratio, 1.14), admission for gastrointestinal (odds ratio, 1.12), respiratory (odds ratio, 1.48) or neurological (odds ratio, 1.65) reasons, and previous ICU admission (odds ratio, 1.18). In patients with a hematological malignancy admitted between 2009 and 2013, hospital mortality was 53.6%. Independent risk factors for hospital mortality were age (odds ratio, 1.02), cardiopulmonary resuscitation before ICU admission (odds ratio, 1.90), Intensive Care National Audit & Research Centre Physiology Score (odds ratio, 1.12), admission for hematological (odds ratio, 1.48) or respiratory (odds ratio, 1.56) reasons, bone marrow transplant (odds ratio, 1.53), previous ICU admission (odds ratio, 1.43), and mechanical ventilation within 24 hours of admission (odds ratio, 1.33). Trend analysis showed a significant decrease in ICU and hospital mortality and length of stay between 1997 and 2013 despite little change in severity of illness during this time. Conclusions: Between 1997 and 2013, the outcome of cancer patients with an unplanned admission to ICU improved significantly. Among those admitted between 2009 and 2013, independent risk factors for hospital mortality were age, severity of illness, previous cardiopulmonary resuscitation, previous ICU admission, metastatic disease, and admission for respiratory reasons. Abstract : Supplemental Digital Content is available in the text.